Effect of cement, sodium silicate, kaolinite and water on the viscosity of the grout - Kazemian, Sina; Prasad, Arun; Kim Huat, Bujang; Mohammed, Thamer Ahmed; Abd. Aziz, Farah Nora Aznieta (Academic Journals, 2010)
Cement, sometimes with/without other binders, is widely used for the stabilization of soil by injection and grouting methods. Chemical grouts and sodium silicate are commonly used worldwide for stabilizing soft soils. This article presents the effectiveness of using cement, sodium silicate, water and kaolinite on the viscosity of the grout. Different samples with different ratio of grout components were prepared and the changes in the viscosity of grout were evaluated. The results showed that by increasing cement, kaolonite and sodium silicate, the viscosity of grout increased; on the other hand, it decreased with an increase in water. The effect of kaolinite on the grout viscosity was investigated is more than that with cement and the behaviour of grout without sodium silicate was observed to be similar to the thixotropy fluid behaviour, and it was similar to rheopexy fluid behaviour with high amount of sodium silicate.